2008
DOI: 10.1096/fj.08-115170
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the coiled‐coil domain with glycosaminoglycans protects angiopoietin‐like 4 from proteolysis and regulates its antiangiogenic activity

Abstract: Angiopoietin-like 4 (ANGPTL4) is involved in angiogenesis and lipid metabolism. It is secreted by liver and adipose tissues and cleaved to generate circulating coiled-coil domain (CCD) and fibrinogen-like domain (FLD) fragments. The full-length ANGPTL4 produced by hypoxic endothelial cells interacts with the extracellular matrix (ECM). The ECM-bound and soluble forms of ANGPTL4 have antiangiogenic properties. We carried out a structure-function analysis to investigate the regulation of ANGPTL4 bioactivity in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 26 publications
9
54
1
1
Order By: Relevance
“…Although its secretion has been shown to modulate the disposition of circulating triglycerides by inhibiting lipoprotein lipase, its role in vascular biology is less clear. ANGPTL4 (or specific domains of the protein) has been shown to regulate endothelial cell adhesion (24) and to promote angiogenesis under some circumstances (21,22,35), but also to inhibit angiogenesis in other circumstances (23)(24)(25)(26). More recently, several studies have suggested similarly discordant functions for this factor in tumor dissemination: whereas systemic ANGPTL4 secretion in mice inhibited melanoma metastasis through inhibition of vascular permeability and tumor cell invasiveness (29), TGFβ-mediated induction of ANGPTL4 by breast cancer cells primed these cells for lung metastasis by increasing the permeability of lung capillaries (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although its secretion has been shown to modulate the disposition of circulating triglycerides by inhibiting lipoprotein lipase, its role in vascular biology is less clear. ANGPTL4 (or specific domains of the protein) has been shown to regulate endothelial cell adhesion (24) and to promote angiogenesis under some circumstances (21,22,35), but also to inhibit angiogenesis in other circumstances (23)(24)(25)(26). More recently, several studies have suggested similarly discordant functions for this factor in tumor dissemination: whereas systemic ANGPTL4 secretion in mice inhibited melanoma metastasis through inhibition of vascular permeability and tumor cell invasiveness (29), TGFβ-mediated induction of ANGPTL4 by breast cancer cells primed these cells for lung metastasis by increasing the permeability of lung capillaries (28).…”
Section: Discussionmentioning
confidence: 99%
“…In KS, this increased vessel permeability manifests with extravasated erythrocytes and inflammatory cells, whereas in other cancers, ANGPTL4 promotes tumor metastasis. Nonetheless, recent evidence also suggests that the biologic functions of ANGPTL4 may be highly dependent on its microenvironment (26). Indeed, the diverse and often contradictory functions of ANGPTL4 may be suggestive of a context or tissue-specific activity for this protein (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies in endothelial and human embryonic kidney 293 (HEK293) cells showed that ANGPTL4 is cleaved after a conserved basic sequence (-RXKR-), and mutation of all four of these amino acids abolishes the cleavage of ANGPTL4 in vitro and in vivo (15,16). ␣1-Antitrypsin Portland variant (␣1-PDX), which was generated by mutating the reactive-site loop of ␣1-antitrypsin to contain the minimal consensus sequence for proprotein convertase (PC) cleavage (-RIPR-), acts as a competitive inhibitor of several PCs (16) and can partially block the processing of ANGPTL4 in human umbilical vein endothelial cells (HUVECs).…”
mentioning
confidence: 99%
“…␣1-Antitrypsin Portland variant (␣1-PDX), which was generated by mutating the reactive-site loop of ␣1-antitrypsin to contain the minimal consensus sequence for proprotein convertase (PC) cleavage (-RIPR-), acts as a competitive inhibitor of several PCs (16) and can partially block the processing of ANGPTL4 in human umbilical vein endothelial cells (HUVECs). Thus, PCs are suspected to act as the enzymes that cleave ANGPTL4.…”
mentioning
confidence: 99%